An analysis of medical waste management practices in the health care sector in Colombo - Gunawardana, K. D. (Management of Environmental Quality: An International Journal, 2018)
Purpose – The purpose of this paper is to identify the type of waste generation and the management of waste in order to reduce pollution in the health care sector with special reference to Colombo, Sri Lanka. The paper further aims to determine the relationship between top management and staff attitudes toward waste management and to identify the level of technology used in medical waste management in various types of health care organizations. Design/methodology/approach – A survey questionnaire was developed using the designed conceptual framework to achieve the objectives of the study. Findings – The study identifies that, though governments provide legislations and regulatory support, organizations of any size must have a positive attitude, awareness, capability and technology to initiate improvements for waste management processes and be prepared to adapt to new trends. Developing positive attitudes and improved knowledge on changes in waste management technology will assist in encouraging organizations to invest in this area. Research limitations/implications – The scope of this project is limited to private health care institutions in the Colombo district in Sri Lanka from where data were gathered. Originality/value – Health care center waste management is a relatively new discipline in the Sri Lankan health sector. This study provides an opportunity for management to identify the level of waste generated by health care institutions and the methods followed for the disposal of waste. Environmental groups can gain benefit through this project, since they can identify whether the private institutes in the health care sector are following world-accepted methods in disposing of waste.
Keywords: Waste management, Environmental pollution, Medical waste, Capital requirement